Genetic structure of the long-snouted seahorse, Hippocampus guttulatus, in the Central–Western Mediterranean Sea. (1st July 2020) - Lazic, Tamara; Pierri, Cataldo; Cardone, Frine; Cariani, Alessia; Colangelo, Paolo; Corriero, Giuseppe; Ferrari, Alice; Marzano, Marinella; Messinetti, Silvia; Pesole, Graziano; Senczuk, Gabriele; Santamaria, Monica; et al.
Abstract: The seahorse Hippocampus guttulatus reaches its highest abundance in confined environments, where it has unique biological and ecological traits that suggest significant genetic differentiation among populations. In the present study, we aimed to reveal the genetic structure of this species by analysing eight microsatellite loci and a mitochondrial DNA region (cytochrome b) of eight populations from the Central–Western Mediterranean Sea, including lagoon sites. Levels of genetic diversity, as measured by the total number of alleles, number of private alleles, allelic richness and heterozygosity, ranged from low to moderate. The overall value of inbreeding was high, indicating a deficiency in heterozygotes. The haplotype network had a star-like construction, with the most common haplotype present in all populations. Data from the two molecular markers congruently displayed a similar pattern and revealed low genetic differentiation, notwithstanding predictions based on species traits. The observed genetic structure is probably the result of both historical population demographic events and current gene flow. The investigated lagoons, however, revealed a unique genetic profile, which is especially highlighted by the Taranto population. At this site, the results also showed altered values of observed/expected heterozygosity and allelic richness, a characteristic of marginal populations. Our study suggests that lagoon populations should be managed as distinct genetic units.